PERSEDIAAN BARANG DI PERCETAKAN PT. HONGKONG RAYA PRIMA - Al Fauzi, Tito Bahtiar; Andrianto, Herlen; Satria, Yasir Joko (Pogram Studi Sistem Komputer Universitas Serang Raya, 2025)
â€œInventory of Goods in Printing at PT. WEB Based Hongkong Raya Prima (Case Study: PT. Hongkong Raya Prima)â€. The increasingly rapid progress of information technology and the potential for its widespread use opens up opportunities for accessing, managing and utilizing large volumes of information quickly and accurately. Designing an Inventory Information System is useful for helping companies manage merchandise inventory, this is very important for trading companies and manufacturing companies. Inventory is needed to create sales to generate profits. Inventory is a current asset that has quite a high risk in the company's activities if it is not paid proper attention, the process of inventorying goods at PT. Hongkong Raya Prima can be said to still be less efficient and effective because everything is still done manually, starting from the process of recording goods data, the process of incoming goods data and outgoing goods data, and the process of reporting goods data. This access does not yet have a good inventory information system, also for ordering data to Suppliers there is no minimum stock data specified so that orders can be made to Suppliers. This results in stock sometimes running out of stock before ordering from Suppliers, and causing delays in goods if there is a purchase from a customer. Therefore, the program application is an alternative solution to problems faced by companies or agencies, especially PT. Hongkong Raya Prima in this case, specially making inventory reports. With this programming application, filling in and storing data will be easier and safer.